Review of food system research - He, Juan; Chen, Yapin; Wu, Shisong (International Journal of Social Sciences and Public Administration, 2024)
In recent years, under the trend of domestic carbon peak, carbon neutral as the environmental goal and global sustainable development, food system, as an important issue closely related to human life has gradually entered the research vision of scholars. This paper uses the literature review method to summarize the research context of food system at home and abroad, and analyzed and predict the future research hotspots and trends of food system, in order to provide theoretical reference for the optimal development of healthy food system in China in the future. This paper holds that: (1) the concept of food system has evolved to a mature stage, and the research is more diverse, and more attention to the relationship between food system and community vitality, cultural retention, economic development, social justice, environmental quality, ecological integration and human health.(2) At present, the research theories and methods of food system mainly focus on structuralism, positivism and humanism.(3) The resilience of food system in the post-epidemic era, the transformation of food system in China and the development of local food system will become the research hotspot of food system in recent years.